THE EFFECT OF USING CALCIUM CHLORIDE IN G CLASS CEMENT ON STARTING TIME AND CEMENT PRESSURE - Cahaya Rosyidan (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Drilling operations always require fluid in their activities. Because to penetrate the soil and rocks will be very easy with the use of fluid. The fluid will help soften the soil and rocks making it easier for the drill bit to penetrate it. Drilling fluid is also needed to attach the casing to the drill wall. So that the wall does not collapse, as media logging and so on. Of course, each drilling zone (surface zone, intermediate zone, and production zone) has different characteristics and different additive substances are needed. This study wants to find out the function of the use of calcium chloride additives on the nature of cement hardness and choking time. This research is important because it will be known this addictive nature as a retarder or accelerator. By knowing the nature of this additive so that it can be used in the right zone. Testing on Calcium Chloride additive for the value of compressive strength is very effective at a concentration of 8%, 24-hour immersion time and a temperature of 150 ° F with a test result of 4483 psi. Whereas, at temperatures of 80 ° F and 100 ° F, the maximum value of compressive strength for Calcium Chloride additive occurs at a concentration of 10% with a test result of 2393 psi and 2888 psi. Based on the data presented, temperature plays an important role in testing the thickening time of a cement sample. The addition of calcium chloride additive functions as an accelerator.